2021
DOI: 10.1002/lio2.693
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress promotes local immunoglobulin E production in allergic rhinitis

Abstract: Background The role of endoplasmic reticulum (ER) stress in the pathogenesis of allergic rhinitis (AR) remains elusive. Methods Real‐time polymerase chain reaction (RT‐PCR), immunohistochemistry, and western blotting analyses were performed to detect the expression of ER stress and unfolded protein response markers: 78‐kDa glucose‐regulated protein (GRP78), C/EBP homologous protein (CHOP), activating transcription factor 6 (ATF6α), spliced X‐box binding protein 1 (sXBP‐1), and phosphorylated eukaryotic initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Furthermore, pharmacological suppression of ER stress through the administration of the chemical chaperone, 4-PBA, has been shown to attenuate the asthmatic features of OVA-sensitized and OVA-challenged mice and reduce IgE production in ex vivo cultures derived from allergic rhinitis (AR) patient's nasal tissue. 52,53 In addition to attenuating early phase mast cell degranulation, we found that treatment with CDN1163 differentially reduced the secretion of various late phase, proinflammatory cytokines/chemokines following allergen stimulation. Here, we show that CDN1163 treatment reduced the secretion of IL-6, IL-13, and CCL3, while TNF, CCL1, and CCL2 secretion remained unaffected, indicating a role for SERCA in the late phase response as well.…”
Section: Mapk Signaling Through Selective Inhibition Of P38mentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, pharmacological suppression of ER stress through the administration of the chemical chaperone, 4-PBA, has been shown to attenuate the asthmatic features of OVA-sensitized and OVA-challenged mice and reduce IgE production in ex vivo cultures derived from allergic rhinitis (AR) patient's nasal tissue. 52,53 In addition to attenuating early phase mast cell degranulation, we found that treatment with CDN1163 differentially reduced the secretion of various late phase, proinflammatory cytokines/chemokines following allergen stimulation. Here, we show that CDN1163 treatment reduced the secretion of IL-6, IL-13, and CCL3, while TNF, CCL1, and CCL2 secretion remained unaffected, indicating a role for SERCA in the late phase response as well.…”
Section: Mapk Signaling Through Selective Inhibition Of P38mentioning
confidence: 84%
“…In mast cells, ROS is known to play a role in degranulation, 50 and levels of ROS have been found to be elevated in asthma patients, with both endogenous and exogenous ROS reported to mediate airway inflammation 51 . Interestingly, increased levels of ER stress markers were recently observed in the lung tissue of bronchial asthmatic mice, 52 as well as the nasal mucosa of atopic dermatitis (AD) patients, and has been demonstrated to promote IgE production, 53 suggesting a potential link between ER stress and ROS production in the pathophysiology of allergic inflammation. Furthermore, pharmacological suppression of ER stress through the administration of the chemical chaperone, 4‐PBA, has been shown to attenuate the asthmatic features of OVA‐sensitized and OVA‐challenged mice and reduce IgE production in ex vivo cultures derived from allergic rhinitis (AR) patient's nasal tissue 52,53 …”
Section: Discussionmentioning
confidence: 99%
“…Hoffman et al believed that house dust mites could induce ERS in respiratory epithelial cells, and transmembrane protein-activated transcription factor 6 (ATF6) played an important role in the pathogenesis of airway allergic diseases including AR [42]. Besides, Liu et al [43] found that ERS may be involved in the production and regulation of local IgE in patients with AR, suggesting that inhibiting ERS to reduce the production of local IgE may provide a new approach for the treatment of AR. Interestingly, it has been reported that specific neurokinin receptor agonists (e.g., SP) stimulate inositol phosphate synthesis and increase intracellular Ca2+ concentrations in human airway smooth muscle cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have emphasized the use of next-generation sequencing (NGS) and quantitative real-time PCR (qRT-PCR) in advanced respiratory disease diagnostics, their role in LAR remains elusive. Furthermore, the current biomarker for the clinical use of LAR remains the level of the local IgE [46,47].…”
Section: Diagnostic Work Upmentioning
confidence: 99%